2018
DOI: 10.1186/s13058-018-1013-z
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide deficiency and endothelial–mesenchymal transition of pulmonary endothelium in the progression of 4T1 metastatic breast cancer in mice

Abstract: BackgroundMesenchymal transformation of pulmonary endothelial cells contributes to the formation of a metastatic microenvironment, but it is not known whether this precedes or follows early metastasis formation. In the present work, we characterize the development of nitric oxide (NO) deficiency and markers of endothelial–mesenchymal transition (EndMT) in the lung in relation to the progression of 4T1 metastatic breast cancer injected orthotopically in mice.MethodsNO production, endothelial nitric oxide syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 49 publications
4
58
0
Order By: Relevance
“…Therefore, the H&E staining images of representative sections of lungs are illustrated (Figure 5C). Typical tumor nodules were observed in the saline group, visualizing the metastasized cancer cells and their localization, as reported previously 35,36. Smaller and fewer nodules were found in lungs with IFN‐γ and NP‐TOS15 treatment, indicating the lung metastasis was inhibited to some degree.…”
Section: Resultssupporting
confidence: 83%
“…Therefore, the H&E staining images of representative sections of lungs are illustrated (Figure 5C). Typical tumor nodules were observed in the saline group, visualizing the metastasized cancer cells and their localization, as reported previously 35,36. Smaller and fewer nodules were found in lungs with IFN‐γ and NP‐TOS15 treatment, indicating the lung metastasis was inhibited to some degree.…”
Section: Resultssupporting
confidence: 83%
“…Recent studies utilizing the model of mouse mammary gland cancer 4T1, reflecting a basal-like phenotype (in human: negative for nuclear estrogen receptor (ER) α, progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2), i.e., triple-negative, and positive for epidermal growth factor receptor (EGFR)) [1][2][3][4], have shown a predominant role of endothelium damage during the metastatic process of these cells [5][6][7]. For instance, it is evidenced that endothelial dysfunction in the lungs, which was assessed as decreased activity and phosphorylation of endothelial nitric oxide synthase (eNOS) resulting in a low nitric oxide (NO) production state, was an early event in breast Literature data [4] and our histopathological analyses confirmed that no cancer cells were detected in the lungs of 67NR tumor-bearing mice ( Figure S1A).…”
Section: Introductionmentioning
confidence: 99%
“…RBP4 enhances the metastatic potential of breast cancer tumors through a direct effect on cancer cells and through increased endothelial dysfunction and impairment of blood vessels within the tumor.Cancers 2020, 12, 623 2 of 21 cancer pulmonary metastasis. These processes precede the onset of a phenotypic switch in the lung endothelium toward a mesenchymal phenotype (EndMT), which is parallel to the appearance of the first pulmonary metastatic colonies [7]. Therefore, therapeutic strategies that aim to normalize endothelial dysfunction can decrease the metastatic potential of this type of breast cancer [8][9][10].Apart from its involvement in cancer development, endothelial dysfunction plays an important role in the development of cardiovascular diseases and atherosclerosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have reported that NOS3 might play an anticancer role in malignant tumours. Research by Smeda et al reported that NOS3 activity and phosphorylation reduction was an early event in the lung metastasis of breast cancer, preceding the onset of the mesenchymal phenotype (EndMT) (25). NOS3 participated in the enhancement of Taxol chemosensitivity with astragaloside IV treatment in breast cancer as a downstream target of caveolin-1 (26).…”
Section: Introductionmentioning
confidence: 99%